CRISPR-Cas9 Approach Constructing Cellulase sestc-Engineered Saccharomyces cerevisiae for the Production of Orange Peel Ethanol - Yang, Peizhou; Wu, Yun; Zheng, Zhi; Cao, Lili; Zhu, Xingxing; Mu, Dongdong; Jiang, Shaotong (Frontiers in Microbiology, 2018)
The development of lignocellulosic bioethanol plays an important role in the substitution of petrochemical energy and high-value utilization of agricultural wastes. The safe and stable expression of cellulase gene sestc was achieved by applying the clustered regularly interspaced short palindromic repeats-Cas9 approach to the integration of sestc expression cassette containing Agaricus biporus glyceraldehyde-3-phosphate-dehydrogenase gene (gpd) promoter in the Saccharomyces cerevisiae chromosome. The target insertion site was found to be located in the S. cerevisiae hexokinase 2 by designing a gRNA expression vector. The recombinant SESTC protein exhibited a size of approximately 44 kDa in the engineered S. cerevisiae. By using orange peel as the fermentation substrate, the filter paper, endo-1,4-β-glucanase, exo-1,4-β-glucanase activities of the transformants were 1.06, 337.42, and 1.36 U/mL, which were 35.3-fold, 23.03-fold, and 17-fold higher than those from wild-type S. cerevisiae, respectively. After 6 h treatment, approximately 20 g/L glucose was obtained. Under anaerobic conditions the highest ethanol concentration reached 7.53 g/L after 48 h fermentation and was 37.7-fold higher than that of wild-type S. cerevisiae (0.2 g/L). The engineered strains may provide a valuable material for the development of lignocellulosic ethanol.